SMYD3 promotes cancer invasion by epigenetic upregulation of the metalloproteinase MMP-9 (2012)
ABSTRACT: Upregulation of the matrix metalloproteinase (MMP)–9 plays a central role in tumor progression and metastasis by stimulating cell migration, tumor invasion, and angiogenesis. To gain insights into MMP-9 expression, we investigated its epigenetic control in a reversible model of cancer that is initiated by infection with intracellular Theileria parasites. Gene induction by parasite infection was associated with trimethylation of histone H3K4 (H3K4me3) at the MMP-9 promoter. Notably, we found that the H3K4 methyltransferase SMYD3 was the only histone methyltransferase upregulated upon infection. SMYD3 is overexpressed in many types of cancer cells, but its contributions to malignant pathophysiology are unclear. We found that overexpression of SMYD3 was sufficient to induce MMP-9 expression in transformed leukocytes and fibrosarcoma cells and that proinflammatory phorbol esters further enhanced this effect. Furthermore, SMYD3 was sufficient to increase cell migration associated with MMP-9 expression. In contrast, RNA interference–mediated knockdown of SMYD3 decreased H3K4me3 modification of the MMP-9 promoter, reduced MMP-9 expression, and reduced tumor cell proliferation. Furthermore, SMYD3 knockdown also reduced cellular invasion in a zebrafish xenograft model o cancer. Together, our results define SMYD3 as an important new regulator of MMP-9 transcription, and they provide a molecular link between SMYD3 overexpression and metastatic cancer progression.